(untitled) (The Review of Diabetic Studies, 2025)
Effective coordination among medical departments is increasingly recognized as a cornerstone of high-quality healthcare systems. Fragmented care processes often contribute to delayed diagnoses, inconsistent treatment plans, increased medical errors, and reduced patient satisfaction. This systematic review examines how interdepartmental medical coordination enhances patient outcomes and reduces clinical risk across diverse healthcare settings. Databases including PubMed, Scopus, Web of Science, and CINAHL were systematically searched for studies published between 2016 and 2025. A total of 67 studies met the inclusion criteria. Results demonstrate that collaborative care ecosystems—defined by structured communication channels, shared decision-making frameworks, integrated care pathways, and interoperable health information systems—significantly improve treatment accuracy, reduce adverse events, strengthen continuity of care, and increase patient satisfaction. The review also identifies key mechanisms underlying these improvements, including improved workflow integration, early risk detection, and multidisciplinary clinical oversight. However, barriers such as role ambiguity, digital fragmentation, and poor communication remain prevalent. This review concludes that interdepartmental collaboration is a vital strategy for healthcare transformation and recommends adopting standardized communication protocols, shared governance structures, and integrated health information systems to optimize patient outcomes and minimize clinical risk.